2021
DOI: 10.3389/fcell.2020.616747
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of TRIM6 Activates the mTORC1 Pathway by Regulating the Ubiquitination of TSC1-TSC2 to Promote Renal Fibrosis

Abstract: Renal fibrosis is considered as the final pathway of all types of kidney diseases, which can lead to the progressive loss of kidney functions and eventually renal failure. The mechanisms behind are diversified, in which the mammalian target of rapamycin (mTOR) pathway is one of the most important regulatory pathways that accounts for the disease. Several processes that are regulated by the mTOR pathway, such as autophagy, epithelial-mesenchymal transition (EMT), and endoplasmic reticulum (ER) stress, are tight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…Epithelial-mesenchymal transition (EMT) is strongly implicated in tumor cell migration, invasion, and metastasis ( 35 ). Snail1 and Twist1, two markers of EMT, and MMP2, a marker of invasion and migration, which could degrade the extracellular matrix, were downregulated in TRIM6 knockdown CRC cells, which is consistent with a study on TRIM6 in renal fibrosis ( 36 ). In this perspective, TRIM6 stimulates the EMT and production of MMP2, which could facilitate tumor cell migration, invasion, and metastasis, thus, causes tumor recurrence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Epithelial-mesenchymal transition (EMT) is strongly implicated in tumor cell migration, invasion, and metastasis ( 35 ). Snail1 and Twist1, two markers of EMT, and MMP2, a marker of invasion and migration, which could degrade the extracellular matrix, were downregulated in TRIM6 knockdown CRC cells, which is consistent with a study on TRIM6 in renal fibrosis ( 36 ). In this perspective, TRIM6 stimulates the EMT and production of MMP2, which could facilitate tumor cell migration, invasion, and metastasis, thus, causes tumor recurrence.…”
Section: Discussionsupporting
confidence: 91%
“…TRIM family proteins are reported to have a E3 ubiquitin ligase activity ( 38 ). Recent studies have reported that TRIM6 promoted the ubiquitination of TIS21 ( 16 ) and TSC1-TSC2 ( 36 ). TRIM6 interacts with SOCS2, and the level of SOCS2 ubiquitination was lower in TRIM6 knockdown HCT116 cells ( Figure 4 ), whereas the ubiquitination site on SOCS2 is to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…1g), which indicated that Everolimus induced the secretion of miR-7-5p-loaded exosomes into the surrounding extracellular environment, resulting in the loss of miR-7-5p in intracellular. Furthermore, we performed siTSC1/2 to active 13 but Everolimus to inhibit the activity of mTORC1. After con rming the expression of mTOR, TSC1 and TSC2 following indicated treatments (Figure S1b), we discovered miR-7-5p was more enriched in exosomes than in intracellular when Everolimus was employed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we performed siTSC1/2 to active [22] but Everolimus to inhibit the activity of mTORC1. After con rming the expression of mTOR, TSC1 and TSC2 following indicated treatments (Figure S1B), we found that miR-7-5p was more enriched in exosomes than in intracellular when Everolimus was employed.…”
Section: Resultsmentioning
confidence: 99%
“…1G), which indicated that Everolimus induced the secretion of miR-7-5p-loaded exosomes into the surrounding extracellular environment, resulting in the loss of miR-7-5p in intracellular. Furthermore, we performed siTSC1/2 to active [22] but Everolimus to inhibit the activity of mTORC1. After con rming the expression of mTOR, TSC1 and TSC2 following indicated treatments (Figure S1B), we found that miR-7-5p was more enriched in exosomes than in intracellular when Everolimus was employed.…”
Section: Resultsmentioning
confidence: 99%